2003
DOI: 10.1623/hysj.48.1.125.43479
|View full text |Cite
|
Sign up to set email alerts
|

The concept of rainfall and streamflow normals in West and Central Africa in a context of climatic variability

Abstract: This contribution to the debate on the revision of rainfall and streamflow normals concerns three countries of West Africa: Burkina Faso, Ivory Coast and Mali. The rainfall deficit (15-20% on average in the study area) and the river flow deficit (about 30-50% and sometimes more) observed over the past 30 years in West and Central Africa raise the problem of the reference period that must be considered in estimates of hydrological characteristics. The hypothesis of the concept of "normal" supporting these estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 16 publications
2
30
0
8
Order By: Relevance
“…Paturel et al [52] and Amani and Paturel [53] pointed out the necessary changes to be processed in hydrological regional norms in order to supply engineers with actual figures of rainfall and runoff characteristics, and new methods, able to account for the non-stationarity in hydrological variables.…”
Section: A Marked Increase In Runoff Coefficients and Discharges Of Smentioning
confidence: 99%
“…Paturel et al [52] and Amani and Paturel [53] pointed out the necessary changes to be processed in hydrological regional norms in order to supply engineers with actual figures of rainfall and runoff characteristics, and new methods, able to account for the non-stationarity in hydrological variables.…”
Section: A Marked Increase In Runoff Coefficients and Discharges Of Smentioning
confidence: 99%
“…After the wet 1950s and 1960s, a strong rainfall deficit has been happening since 1970 in the Sahelian and Sudano-Sahelian areas (e.g., Paturel et al, 2003), with some dramatic droughts like the 1973/1974 and 1983/1984 ones. Recent studies such as Lebel and Ali (2009), however, suggest a recovery of the rain in eastern parts of WA, whereas drought conditions endure in western regions.…”
Section: Climate Variability and Changementioning
confidence: 99%
“…Maps depicting the rainfall patterns and trends for the periods 1940/1970 and 1971/1995 are drawn, as several works have given 1970 as the beginning of the rainfall deficit in West Africa on average (Mahe et al, 2001;L'Hote et al, 2002;Paturel et al, 2003b), as shown in the rainfall dataset plot in Figure 4, with the rupture in 1970 according to the different detection tests available in the Khronostat software (Lubes-Niel et al, 1998). The rainfall and runoff changes in 1970 are very well marked over the Bani River (Mahe et al, 2000), and on a larger scale for other rivers of West Africa (Mahe and Olivry, 1999) using the same software.…”
Section: Resultsmentioning
confidence: 99%